Negli occhi dell'Axolotl, ovvero Empatia Astrazione Straniamento (Materiali di Estetica. Terza serie, 2025)
Some short stories in the dazzling production of Cortázar and Borges offer crucial experiments in the narrative translation of the Self in the Other. Methodologically distant but critically integrable theoretical perspectives (from Worringer to Nussbaum) permit us to investigate them as effective and affective paradigm of the Literary form of empathetic practice, in its irreducible complexity.
Keywords: estrangement; cultural appropriation; metamorphosis; emotions